Effects of 8-week thera-band training on spike speed, jump height and speed of upper limb performance of young female volleyball players - Agopyan, A.; Ozbar, N.; Ozdemir, S. N. (International Journal of Applied Exercise Physiology, 2018)
Introduction and objectives: Elastic resistance has been commonly used in the therapeutic and fitness setting. However, the effects of a strength training program using elastic resistance exercises to the explosive power and spike speed, which are very important elements for successful volleyball practice, has not been clearly demonstrated. Therefore, the aim of this study was to establish the effects of 8-week Thera-Band training protocols on the development of spike speed, counter movement jump (CMJ) height, peak power and speed of upper limb performance of young female volleyball players. Methods: The participants consists of 20 competitive female volleyball players who regularly train at the same team and aged 15-17 years (age 16.2 ± 0.7 years). All the players were tested for spike speed, CMJ height, peak power and speed of upper limb performances before and after 8-week training program. The players were divided into Thera-Band Training Group (TTG; n=10) and Control Group (CG; n=10). Both groups continued technical and tactical volleyball training together 3 days (120 min.d.-1) a week. Additionally, TTG attended Thera-Band training program through 8-week, 2 days per week and 2 sessions (60 min.d.-1). Results: The findings of the study showed significant change in CMJ height, peak power and spike speed at the end of 8-week. TTG significantly (p ≤ .001) improved CMJ height, peak power and spike speed, whereas the CG showed significant changes only CMJ height and peak power (p ≤ .05) at the end of 8-week. The effect of resistance exercises was significantly higher as compared to the control group (p < .05). Results demonstrated that the TTG players showed greater improvements in CMJ height (d = 1.31, moderate effect size), and spiking speed (d = 2.93, large effect size) performance than CG. Conclusion: It can be concluded that supervised Thera-Band training contributed development of the performance of spike speed mostly and CMJ height and peak power of lower extremities in young female volleyball players. Due to its effectiveness on muscular performance, the Thera-Band training model can be recommended to the coaches and players in additional to the regular technical training.